2016
DOI: 10.3390/ijms17060875
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Heart-Enriched miR-708 Promotes Differentiation of Cardiac Progenitor Cells in Rats

Abstract: Cardiovascular disease is becoming the leading cause of death throughout the world. However, adult hearts have limited potential for regeneration after pathological injury, partly due to the quiescent status of stem/progenitor cells. Reactivation of cardiac stem/progenitor cells to create more myocyte progeny is one of the key steps in the regeneration of a damaged heart. In this study, miR-708 was identified to be enriched in the neonatal cardiomyocytes of rats, but this has not yet been proven in adult human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Emerging evidence has demonstrated that non-coding miRNAs are capable of maintaining cardiac organ homeostasis and repairing injured heart in adult mammals. 6 , 24 , 25 , 26 A recent publication reported miR-128 serving as a critical regulator of endogenous cardiomyocyte proliferation. 36 Deletion of miR-128 promoted cell cycle re-entry in adult cardiomyocytes, and thereby reduced the levels of fibrosis and attenuated cardiac dysfunction in response to MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that non-coding miRNAs are capable of maintaining cardiac organ homeostasis and repairing injured heart in adult mammals. 6 , 24 , 25 , 26 A recent publication reported miR-128 serving as a critical regulator of endogenous cardiomyocyte proliferation. 36 Deletion of miR-128 promoted cell cycle re-entry in adult cardiomyocytes, and thereby reduced the levels of fibrosis and attenuated cardiac dysfunction in response to MI.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on miRNA screening in cardiomyocytes revealed the enrichment of miR-708 and miR-301a in the heart of neonatal rats and mice. 2 , 26 miR-708 has been demonstrated to promote differentiation of cardiac progenitor cells and promote cardiac myocyte proliferation. 2 , 26 However, the function of miR-301a in cardiomyocytes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we think it is more likely that miR-708 may reactivate the quiescent progenitor cells and promote proliferation of the freshly differentiated cardiomyocytes in adult hearts. Although this has not been demonstrated yet by experimental assays in vivo , our previous work has indicated the differentiation induction of cardiac progenitor cells to cardiomyocytes in vitro 24 .…”
Section: Discussionmentioning
confidence: 87%
“…Compared with non-progenitors, c-kit + CSCs display lower levels of miR-708, the expression of which is markedly upregulated upon CSC differentiation. Overexpression of miR-708 specifically promotes differentiation of CSCs to CMs [40]. In addition, the expression of miR-218 is upregulated during CSC differentiation into CMs.…”
Section: Mirna Signature and Function In Cardiac Stem Cellsmentioning
confidence: 99%